Narrative form - Keen, Suzanne, 1973- (Palgrave Macmillan, 2015)
"This revised and expanded handbook concisely introduces narrative form to advanced students of fiction and creative writing, with refreshed references and new discussions of cognitive approaches to narrative, nonfiction, and narrative emotions. Beginning with an updated survey of major theorists and approaches, and using clearly defined terms, Narrative Form explains critical vocabulary and offers a variety of strategies for analyzing the formal qualities of narrative. Narrative Form shows how to use the language of formal analysis accurately and innovatively when discussing fictional and nonfictional narratives in a variety of media: stories, novels, films, graphic narratives, and video games"--
Keywords: naratologie; vypravěčské techniky; fikce; narratology; narrative techniques; fiction; příručky; handbooks, manuals, etc